Advanced Solid Biofuel Production via the Integration of Torrefaction and Densification and its Characterization for the Direct Coal Substitution in Energy Intensive Industries - Gaudet, Peter George (Université d'Ottawa / University of Ottawa, 2019)
The greatest political, scientific, and engineering challenge of the 21st century is finding a viable solution to limit anthropogenic greenhouse gas emissions (CO2) to curb the effects of global climate change. All sectors of society need to contribute to alleviate this problem, but industrial operations must play a significant leadership role. Some of these industries include: metallurgy, cement, power, agriculture and forestry. In particular, the iron/steel, cement, and power generation industries use coal on account of its high energy density among solid fuels. Coal combustion yields 720 tonne CO2/GWh, and produces fine particulates, sulphur and nitrous oxides, along with excess CO2 contributing to climate change. In comparison, biomass (such as agricultural and forestry residues) has a solid fuel rating of 25-100 tonne CO2/GWh; therefore, biomass fuels are considered more sustainable since the living biomass consumed CO2 in the early part of its life cycle. However, biomass has significant industrial shortcomings for its use as fuel at large scale, including low energy content, density, and hydrophobicity relative to coal. In short, biomass fuels cannot be substituted without major infrastructure changes which add economic penalties that industry is currently unwilling to absorb. Biomass upgrading routes were considered in this thesis. These include densification, torrefaction, and integrated torrefaction and densification (ITD). The first half of the methodology involved converting woody biomass (willow residue and poplar bark), agricultural residue (switchgrass plants), and pulp mill waste via a single pellet/briquette press at different densification temperatures and pressures. The second half of the methodology involved product characterization of each batch of pellets and briquettes. In this work, pellets and briquettes were tested for physical characteristics (density and durability), chemical differences (energy content and hydrophobicity), and transport phenomena characteristics (drying profiles). First, results showed that extrusion of torrefied biomass at 300°C with an estimated pressure of 10 MPa creates partially formed pellets from agricultural residues. Using the concept of ITD (temperature range 220-325°C and pressure range 40 and 215 MPa), the density was found to be 1000-1250 kg/m3 for pellets and briquettes. The degree of compression from the loose biomass was on the order of 3-10 which corresponds with theoretical expectations. Material density increased with increasing pressure. The solid yield of pellets and briquettes decreased with increasing temperature, and results aligned with micro-scale thermogravimetric analysis. The larger ITD briquettes (produced at T = 325°C, P = 40 MPa) were evaluated for calorific value and found to fall in the lignite classification (O/C < 0.4 and H/C < 1.2) on a van Krevelen diagram. The resulting ITD pellets and briquettes were found to have a durability similar to commercial materials (durability > 97%), and to be more hydrophobic (8 wt% moisture absorption compared to 35 wt%). The drying time of ITD materials was faster than commercial torrefied briquettes, with an effective diffusivity of 1.5×10-6 m2/s compared to 7.3×10-9 m2/s likely because of a smaller pore volume in ITD briquettes. Further pilot scale studies would help improve the ITD methodology and make the process more appealing for the replacement of coal fuels.
Keywords: Torrefaction; Densification; Durability; Hydrophobicity; Advanced Solid Biofuel; Coal Substitution; Iron/Steel Industry; Electric Power Generation